2018
DOI: 10.1530/erp-18-0024
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of British and American Society of Echocardiography recommendations for the assessment of left ventricular diastolic function

Abstract: At present there are two recognised guidelines for the echocardiographic assessment of left ventricular diastolic function provided by the British Society of Echocardiography and American Society of Echocardiography/European Association of Cardiovascular Imaging. However, no direct comparison of these guidelines has been performed to establish whether they provide similar diastolic grading. One hundred and eighty-nine consecutive patients in sinus rhythm who underwent transthoracic echocardiography for a prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Examination of these individual markers is clinically relevant, since an indeterminate classification using the ESC/EACVI algorithm was common (affecting 21.5% of individuals overall and 62.2% of the reduced LVEF category), raising a clinical dilemma if the guideline recommendations are used in isolation. Our finding of a frequent indeterminate classification is similar to other studies, 7 , 8 , 14 although after exclusion of patients with cardiomyopathy, valvular heart disease, and non-sinus rhythm, indeterminate diastolic function is less frequently allocated. Since DD is associated with future HF and mortality, 15 , 16 allocation to indeterminate diastolic function has clinical relevance, especially considering our demonstration of increased mortality in the indeterminate preserved LVEF groups, and a similar demonstration by Liang et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Examination of these individual markers is clinically relevant, since an indeterminate classification using the ESC/EACVI algorithm was common (affecting 21.5% of individuals overall and 62.2% of the reduced LVEF category), raising a clinical dilemma if the guideline recommendations are used in isolation. Our finding of a frequent indeterminate classification is similar to other studies, 7 , 8 , 14 although after exclusion of patients with cardiomyopathy, valvular heart disease, and non-sinus rhythm, indeterminate diastolic function is less frequently allocated. Since DD is associated with future HF and mortality, 15 , 16 allocation to indeterminate diastolic function has clinical relevance, especially considering our demonstration of increased mortality in the indeterminate preserved LVEF groups, and a similar demonstration by Liang et al .…”
Section: Discussionsupporting
confidence: 91%
“…For example, it has been reported that between 20% and 50% of patients have ‘indeterminate’ diastolic function if guideline algorithms are applied. 7 , 8 Moreover, normal age-related changes are not considered. In this context identifying high-risk individuals with DD remains a priority.…”
Section: Introductionmentioning
confidence: 99%
“… Perfusion of the intertrabecular recesses from the LV cavity. Differentiation between false chords, aberrant bands, and trabeculations in the apical four-chamber view, as well as atypical views to obtain the best image quality [1] , [15] . …”
Section: Methodsmentioning
confidence: 99%
“…Further real-world clinical data from Europe (1,000 individuals), Britain (189 individuals), Asia (57,630 individuals), America (866 individuals), and Canada (71,727 individuals), show that even after excluding patients with diastology-confounding factors, between 11 and 22% of scans are labelled indeterminate ( 5 , 18 , 19 , 21 , 22 ). A pertinent limitation of the literature base collectively is that a breakdown of reasons for indeterminate grading is often not presented.…”
Section: Limitations Of Routine Diastolic Assessmentmentioning
confidence: 99%